2019
DOI: 10.1038/s41598-019-56101-x
|View full text |Cite
|
Sign up to set email alerts
|

Care Practices, Morbidity and Mortality of Preterm Neonates in China, 2013–2014: a Retrospective study

Abstract: This retrospective cohort study aimed to investigate the prevalence, morbidity, mortality and the maternal/neonatal care of preterm neonates and the perinatal risk factors for mortality. We included data on 13,701 preterm neonates born in 15 hospitals for the period 2013–2014 in China. Results showed a prevalence of preterm neonates of 9.9%. Most infants at 24–27 weeks who survived more than 12 hours were mechanically ventilated (56.1%). Few infants born before 28 weeks received CPAP without first receiving me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
7
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
9
7
3
Order By: Relevance
“…In the current study, preterm neonates who had perinatal asphyxia (PNA) had a greater hazard of neonatal mortality than those preterm neonates without PNA. This nding is consistent with studies reported from China (22), Gonder (18,19,24), Woliata Sodo (23), Addis Ababa (52), and Jimma, Ethiopia (33,36). This consistency might be elucidated by similarity in study design, and follow-up period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, preterm neonates who had perinatal asphyxia (PNA) had a greater hazard of neonatal mortality than those preterm neonates without PNA. This nding is consistent with studies reported from China (22), Gonder (18,19,24), Woliata Sodo (23), Addis Ababa (52), and Jimma, Ethiopia (33,36). This consistency might be elucidated by similarity in study design, and follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, preterm neonates born from mothers who used antenatal steroids had a lesser hazard of mortality than those neonates born from mothers who did not use antenatal steroids. This nding is in line with studies reported in the United States (20) and China (21,22). This could be explained by the fact that the administration of steroids for mothers who had imminent preterm delivery enhances fetal lung maturity and decreases the risk of developing respiratory distress syndrome and intraventricular hemorrhage, and consequently might reduce the risk of neonatal death (48).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies, we found none of speci c pulmonary diseases was independently associated with the nal outcome [35][36][37]. However, previous studies found mortality was not correlated with lower birth body weight, which may be due to different study population, different therapeutic interventions and various de nition of respiratory failure [35][36][37]. Besides, our data also highlights the important role of initial-HFOV patient characteristics and aggressive treatment of sepsis to prompt neonates toward optimized outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we analyzed a wide variety of patients (i.e., neonates with RDS, severe BPD, and secondary pulmonary hypertension) together. Similar to previous studies, we found none of speci c pulmonary diseases was independently associated with the nal outcome [35][36][37]. However, previous studies found mortality was not correlated with lower birth body weight, which may be due to different study population, different therapeutic interventions and various de nition of respiratory failure [35][36][37].…”
Section: Discussionsupporting
confidence: 85%
“…The predictors of mortality among preterm neonates born at MRRH were largely modifiable and ranged from prenatal, natal and postnatal predictors (lack of ANC attendance or late ANC booking, vaginal breech delivery, birth asphyxia, respiratory distress syndrome and hypothermia at the time of admission to the neonatal unit, not receiving kangaroo mother care and delayed initiation of breastfeeding). Similar findings have been reported from other studies of various settings [34,35,[41][42][43][44][45][46][47]. The predictors found in our study suggest that relatively simple interventions might improve the outcomes of the preterm neonates born at MRRH.…”
Section: Plos Onesupporting
confidence: 92%